The Non-N6-Methyladenosine Epitranscriptome Patterns and Characteristics of Tumor Microenvironment Infiltration and Mesenchymal Transition in Glioblastoma - Xu, Jianye; Gao, Zijie; Liu, Kaining; Fan, Yang; Zhang, Zongpu; Xue, Hao; Guo, Xing; Zhang, Ping; Deng, Lin; Wang, Shaobo; Wang, Huizhi; Wang, Qingtong; et al. (Frontiers in Immunology, 2022)
Background An increasing number of RNA modification types other than N6-methyladenosine (m6A) modification have been detected. Nonetheless, the probable functions of RNA modifications beyond m6A in the tumor microenvironment (TME), mesenchymal (MES) transition, immunotherapy, and drug sensitivity remain unclear. Methods We analyzed the characteristics of 32 non-m6A RNA modification regulators in 539 glioblastoma (GBM) patients and the TME cell infiltration and MES transition patterns. Using principal component analysis, a non-m6A epitranscriptome regulator score (RM score) model was established. We estimated the association between RM score and clinical characteristics, TME status, GBM subtypes, and drug and immunotherapy response. Results Three definite non-m6A RNA modification patterns associated with diverse biological pathways and clinical characteristics were identified. The high RM score group was characterized by a poor prognosis, enhanced immune infiltration, and MES subtype. Further analysis indicated that the high RM score group had a lower tumor mutation burden as well as a weaker response to immunotherapy. The higher RM score group may benefit more from drugs targeting the EGFR and WNT signaling pathways. Conclusion Our study exposed the potential relationship of non-m6A RNA modification regulators with clinical features, TME status, and GBM subtype and clarified its therapeutic value.